IMPLEMENTASI MANAJEMEN PELATIHAN K3 UNTUK MENINGKATKAN KINERJA OPERATOR ALAT BERAT DI PT. ANUGERAH MAKMUR SEJATI - Sumaryanto; Daryanto, Eka; Simanjuntak, Janter Pangaduan; Siregar, Batumahadi (Jurnal Insinyur Profesional, 2024)
One of the objectives of Law No. 1 of 1970 concerning Occupational Safety is that production sources in the workplace can be used and utilized safely and efficiently. Occupational Health and Safety (OHS) training for workers who serve as heavy equipment operators is one of the efforts to improve their performance. The objective of the OHS training for heavy equipment operators at PT. Anugerah Makmur Sejati (AMS) is to improve knowledge, skills and attitudes of heavy equipment operators. With OHS training, it is expected that heavy equipment operators are able to carry out their duties such as carrying out daily routine maintenance and able to operate heavy equipment in accordance with applicable OHS provisions. The purpose of this study is to describe and analyze the application of OHS training management in improving the performance of heavy equipment operators at PT. AMS Kapuas Hulu. Respondents in this study were PT. AMS employees who served as heavy equipment operators with a total of 14 people. The respondents are determined by probability with simple random sampling technique. The data analysis technique in this research is descriptive qualitative in order to describe the management of training workers who serve as heavy equipment operators set by PT. AMS. The results obtained from research at PT. AMS in carrying out training are carried out with management functions, namely; planning, organizing, actuating, and controlling (POAC). Planning which includes needs assessment, proposal submission, goal creation and training design, while controlling includes evaluation.